Robotic prostatectomy: the anesthetist's view for robotic urological surgeries, a prospective study, - Oksar,Menekse (2014)
Background and objectives:Although many features of robotic prostatectomy are similar to those of conventional laparoscopic urological procedures (such as laparoscopic prostatectomy), the procedure is associated with some drawbacks, which include limited intravenous access, relatively long operating time, deep Trendelenburg position, and high intra-abdominal pressure. The primary aim was to describe respiratory and hemodynamic challenges and the complications related to high intra-abdominal pressure and the deep Trendelenburg position in robotic prostatectomy patients. The secondary aim was to reveal safe discharge criteria from the operating room.Methods:Fifty-three patients who underwent robotic prostatectomy between December 2009 and January 2011 were prospectively enrolled. Main outcome measures were non-invasive monitoring, invasive monitoring and blood gas analysis performed at supine (T0), Trendelenburg (T1), Trendelenburg + pneumoperitoneum (T2), Trendelenburg-before desufflation (T3), Trendelenburg (after desufflation) (T4), and supine (T5) positions.Results:Fifty-three robotic prostatectomy patients were included in the study. The main clinical challenge in our study group was the choice of ventilation strategy to manage respiratory acidosis, which is detected through end-tidal carbon dioxide pressure and blood gas analysis. Furthermore, the mean arterial pressure remained unchanged, the heart rate decreased significantly and required intervention. The central venous pressure values were also above the normal limits.Conclusion:Respiratory acidosis and "upper airway obstruction-like" clinical symptoms were the main challenges associated with robotic prostatectomy procedures during this study.